Religion, politics and COVID-19 risk perception among urban residents in Malawi - Emmanuel Chilanga; Mastano Dzimbiri; Patrick Mwanjawala; Amanda Keller; Ruth Agather Mbeya (BMC, 2022)
Abstract Introduction Majority of Malawians have not yet adopted COVID-19 mitigation measures despite having knowledge about its infectivity, morbidity, and fatality. Understanding drivers of hesitancy to adoption of COVID-19 mitigation measures is critical as it can inform prevention programs. This study explores Malawians' COVID-19 risk perception, and the associated constraints in the adoption of mitigation efforts. A Health Belief Model (HBM) approach was used to understand perceived factors that undermine public health COVID-19 messages to reduce the spread of the pandemic in Malawi. Methods The study applied rapid appraisal and photovoice qualitative inquiry to comprehend risk perception regarding COVID-19. We purposively selected 52 participants from three major cities in Malawi. Audio and video interviews were transcribed verbatim, and transcripts were coded manually to derive key themes and concepts. Results The study identified that social factors particularly religious and political beliefs influenced COVID-19 risk perception. Specific religious beliefs pertaining to individuals recognizing signs of the 'Christian apocalypse' were particularly associated with lower risk perceptions. Politically, participants believed COVID-19 lockdown measures were a ploy by the then-ruling party to remain in power. Conclusion The study suggests that religious beliefs and political environment undermine self -perceived risk of contracting COVID-19 among urban dwellers in Malawi. We recommend that diverse actors in Malawi should collaborate to promote the dissemination of accurate COVID-19 discourses and reduce the severity of the pandemic's impact in Malawi.